Experimental work for mechanical properties of brick and masonry panel - Phaiju, Saroj; Pradhan, Prachand Man (Journal of Science and Engineering, 2018)
The use of Masonry panels in building construction has been popular in most of the parts of the world. However, the use of bricks and brick masonry in different parts of the world being of different nature in terms of quality, size, workmanship of construction, etc. It is yet a topic of interest to researchers to identify the mechanical properties, like Young’s modulus of elasticity and shear modulus of brick masonry panels. It is essential to know the characteristic of brick masonry panels in order to evaluate the responses of masonry walls for any kind of loading. Individual bricks do possess better compressive capacity as compared to masonry walls. Masonry walls are bound together with either mud mortar or by cement sand mortars of various mixes as per the strength requirements. The essential strength properties in engineering are basically the compressive strength and the modulus of elasticity. The American Society for Testing and Materials (ASTM) standard is the most popular for testing bricks and brick masonry for these properties so far. Here, the study has been concentrated in finding the compressive strength of brick, mortar and brick masonry. The study is also done for Young’s modulus of elasticity of brick as well as that of masonry wall. Similarly, the study is extended to find the modulus of rigidity of brick masonry panel. The study is done experimentally for the samples that are generally used in Kathmandu, Nepal. The samples include bricks, cement and sand particularly available in Kathmandu region.